Sound Generation Using a Magnetostrictive Micro-Actuator - Albach, Thorsten; Horn, Peter; Sutor, Alexander; Lerch, Reinhard (55th Annual Conference on Magnetism and Magnetic Materials (MMM), 2010)

Sound Generation Using a Magnetostrictive Microactuator - Albach, Thorsten; Horn, Peter; Sutor, Alexander; Lerch, Reinhard (Journal of Applied Physics, 2011)
In this paper, we present the design and performance of a MEMS-device based on the magnetostrictive effect, which can be used as a micro-loudspeaker. The device basically consists of a comb structure of monomorph bending cantilevers with an active area up to 3.0 x 2.5 mm(2). It produces a sound-pressure-level up to 101 dB at 400 Hz in a standard 2 ccm measurement volume. We show our measurement setup as well as a mechanic-acoustic-coupled lumped element model to calculate sound pressure. The model incorporates finite element results for mechanical behavior. Measurement results validate our model assumptions. (C) 2011 American Institute of Physics. [doi:10.1063/1.3554200]

System for spatially resolved sound field measurements - Horn, Peter; Metzger, Jochen; Wüst, Michael; Lerch, Reinhard (Technisches Messen, 2014)
The sound field around a noise emitting device gives information about the position of sound sources and their contribution to the overall emitted noise. Therefore, a measurement system was developed that allows for the fast determination of the sound field. Thereby, the microphone's position is detected and the measured pressure signal is linked with a position in space. The microphone is attached to a handheld marker which is equipped with ultrasonic transmitters. By measuring the time of flight of the ultrasonic signal between the marker and the receiver's position in the room, the microphone's position is determined. Measurements showing the analysis of structural vibration and sound fields around different machinery are presented.
Keywords: Sound field; measurement system; indoor positioning system

Towards a Magnetostrictive Micro-Loudspeaker - Albach, Thorsten; Horn, Peter; Ilg, Jürgen; Friedrich, Stefan; Sutor, Alexander; Lerch, Reinhard (15th Int. Conf. on Sensors and Measurement Technology, SENSOR 2011, 2011)